Effect of Supplementing Rumen Protected Choline and Fat during Transition Period on Body Parameters of Periparturient Gir Cows - Chavda, Miteshkumar Ravjibhai; Harish H. Savsani; Viral V. Gamit; Mahesh R. Gadariya; Ghanshyam P. Sabapara; Deendayal D. Garg; Vijay K. Karangiya; Yash G. Kanasagara; Rinkesh B. Makwana (Indian Journal of Animal Nutrition, 2023)
The present experiment was carried out on 24 advanced pregnant Gir cows to evaluate the effect of peripartum supplementation of rumen protected choline (RPC) and rumen protected fat (RPF) alone and in combination on body parameters of Gir cows. The cows were divided into 4 treatment groups (n=6 in each) on the basis of their parity, body weight and previous lactation yield. Cows in T1 group (control) were fed basal diet, in T2, T3 and T4 groups were additionally supplemented with RPC @ 45 g/day, RPF @ 80 g/d and RPC @ 45 g/day + RPF @ 80 g/d along with basal diet, respectively starting from 30 ± 15 days before expected date of calving to 60 days postpartum. The animals were fed as per ICAR (2013) feeding standard. Overall mean fortnightly body weight (kg) and body condition score were significantly (p